Cytosolic Phospholipase A(2) Activation by Candida albicans in Alveolar Macrophages: Role of Dectin-1 - Parti, Rajinder P. (American Thoracic Society, 2010)
Candida albicans is an increasingly important pulmonary fungal pathogen. Resident alveolar macrophages are important in host defense against opportunistic fungal infections. Activation of Group IVA cytosolic phospholipase A(2)α (cPLA(2)α) in macrophages initiates arachidonic acid (AA) release for production of eicosanoids, which regulate inflammation and immune responses. We investigated the ability of C. albicans to activate cPLA(2)α in unprimed alveolar macrophages and after priming with granulocyte macrophage colony-stimulating factor (GM-CSF), which regulates alveolar macrophage maturation. AA was released within minutes by GM-CSF–primed but not unprimed alveolar macrophages in response to C. albicans, and was blocked by soluble glucan phosphate (S-GP). The expression of the β-glucan receptor dectin-1 was increased in GM-CSF–primed macrophages, and AA release from GM-CSF–primed dectin-1(−/−) alveolar macrophages was reduced to basal levels. The enhanced activation of extracellular signal–regulated kinases and phosphorylation of cPLA(2)α on Ser-505 that occurred in GM-CSF–primed macrophages were reduced by MEK1 and Syk inhibitors, which also suppressed AA release. At later times after C. albicans infection (6 h), unprimed and GM-CSF–primed macrophages released similar levels of AA. The expression of cyclooxygenase 2 and prostanoid production at 6 hours was higher in GM-CSF–primed macrophages, but the responses were not dependent on dectin-1. However, dectin-1 contributed to the C. albicans–stimulated increase in TNF-α production that occurred in GM-CSF–primed macrophages. The results demonstrate that dectin-1 mediates the acute activation of cPLA(2)α in GM-CSF–primed alveolar macrophages, but not in the more delayed phase of AA release and GM-CSF–dependent prostanoid production.